Parents' attitudes, knowledge and practice towards vaccinating their children against COVID-19: a cross-sectional study. Issue 5 (30th November 2022) - Al-Qerem, Walid; Al Bawab, Abdel Qader; Hammad, Alaa; Jaber, Tasneem; Khdair, Sawsan I; Kalloush, Haneen; Ling, Jonathan; Mosleh, Rami
ABSTRACT: The question of whether children should be vaccinated against COVID-19 is currently being argued. The risk-benefit analysis of the vaccine in children has been more challenging because of the low prevalence of acute COVID-19 in children and the lack of confidence in the relative effects of the vaccine and the disease. One of the most convincing arguments for vaccinating healthy children is to protect them from long-term consequences. The aim of this study was to assess Jordanian parents' intention to vaccinate their children. This is an Internet-based cross-sectional survey. The researchers prepared a Google Forms survey and shared the link with a number of Jordanian Facebook generic groups. Data were gathered between September and November 2021. In this study, convenience sampling was used. Knowledge about COVID-19 and preventive practices against COVID-19 were calculated for each participant. A total of 819 participants completed the survey (female = 70.9%). Of these, 274 (30.2%) participants intended to vaccinate their children, whereas the rest were either unsure 176 (21.5%) or intended not to vaccinate their children 396 (48.4%). The variables that increased the odds of answering "No" vs "Yes" to "will you vaccinate your children against COVID-19" included not willing to take the vaccines themselves (OR 3.75; CI, 1.46–9.62) and low protective practice group (OR 1.73;CI, 1.12–2.68). Participants had significant levels of refusal/hesitancy. Several barriers to vaccination were identified; attempts to overcome these should be stepped up.